Tentukan penyelesaian dari a.(-2)×4÷8= b.3÷6×2= c. 2×(-8)÷4= d.(-10) + 8 = e.12 –(-12)= f. 25 + (-3)= g.(-12) –(-23)=
` penyelesaian ` :
a. (- 2) × 4 ÷ 8
=• (- 8) ÷ 8
=• (- 1)
b. 3 ÷ 6 × 2
=• 2 × 2
=• 4
c. 2 × (- 8) ÷ 4
=• (- 16) ÷ 4
=• (- 4)
d. (- 10) + 8
=• (- 2)
e. 12 - (- 12)
=• 12 + 12
=• 24
f. 25 + (- 3)
=• 22
g. (- 12) - (- 23)
=• (- 12) + 23
=• 11
•-Answer By yunlzz-•
Jawaban:
a. (-2) x 4 ÷ 8 = (-2) x 4 = -8
(-8) ÷ 8 = -1
b. 3 ÷ 6 x 2 = 3 ÷ 6 = 0,5
0,5 x 2 = 1
c. 2 x (-8) ÷ 4 = 2 x (-8) = -16
(-16) ÷ 4 = -4
d. (-10) + 8 = -2
e. 12 - (-12) = 12 + 12 = 24
f. 25 + (-3) = 22
g. -12 - (-23) = -12 + 23 = 11
[answer.2.content]